Caracterización de intoxicaciones accidentales con sustancias químicas notificadas en Bogotá D.C. del 2008 al 2016 (2017)
Accidental poisonings are frequent in Bogotá due to the occupational and urban impact of the use of chemical substances, which cover their use from a hairdresser, in a home, even in industries and manufacturing, almost imperceptible are becoming a topic of public health that every day usually climbs by the growth of the city, the population most affected are children under 5 years of age who are victims of these substances due to the fact of learning and cognitive development, also people with low schooling who do not know how to use them and many times due to errors that can be fatal, intoxications .